Exchange server 2010 administration real world skills for MCITP certification and beyond - Stidley, Joel, 1976- (Wiley Technology Pub., 2011)
"A soup-to-nuts guide for messaging administrators. Exchange Server is the world's leading e-mail server software. Windows 7 and Server 2008 R2 have made changes that messaging administrators need to know and understand in their daily work with Exchange Server. This Sybex guide focuses on the skills, concepts, technologies, and potential pitfalls that admins in the trenches need to understand. It also provides the information they need to earn MCITP certification. Updates in Exchange Server, the world's leading e-mail server software, require messaging administrators to update their knowledge in order to provide the best possible e-mail solutions. Highly focused and comprehensive, this guide teaches you to design a highly available e-mail messaging server, install and configure Exchange Server 2010, work with recipients, groups and mailboxes, configure public folders, secure Exchange, and more. CD includesvideo walkthroughs of more difficult tasks, practice exams, and electronic flashcards. Exchange Server 2010 Administration offers real-world knowledge that messaging admins need every day and helps prepare candidates for the MCITP certification exam"--